Ancient Artworks and Crocus Genetics Both Support Saffron’s Origin in Early Greece - Kazemi-Shahandashti, Seyyedeh-Sanam; Mann, Ludwig; El-nagish, Abdullah; Harpke, Dörte; Nemati, Zahra; Usadel, Björn; Heitkam, Tony (Frontiers in Plant Science, 2022)
Saffron crocus (Crocus sativus) is a male-sterile, triploid flower crop and source of the spice and colorant saffron. For over three millennia, it was cultivated across the Mediterranean, including ancient Greece, Persia, and other cultures, later spreading all over the world. Despite saffron crocus’ early omnipresence, its origin has been the matter of a century-old debate, in terms of area and time as well as parental species contribution. While remnants of the ancient arts, crafts, and texts still provide hints on its origin, modern genetics has the potential to efficiently follow these leads, thus shedding light on new possible lines of descent. In this review, we follow ancient art and recent genetics to trace the evolutionary origin of saffron crocus. We focus on the place and time of saffron domestication and cultivation, and address its presumed autopolyploid origin involving cytotypes of wild Crocus cartwrightianus. Both ancient arts from Greece, Iran, and Mesopotamia as well as recent cytogenetic and comparative next-generation sequencing approaches point to saffron’s emergence and domestication in ancient Greece, showing how both disciplines converge in tracing its origin.